De-Identification of Clinical Notes Using Contextualized Language Models and a Token Classifier - Santos, Joaquim; Santos, Henrique D. P. dos; Tabalipa, Fábio; Vieira, Renata (Anais da Brazilian Conference on Intelligent Systems (BRACIS), 2021)
The de-identification of clinical notes is crucial for the reuse of electronic clinical data and is a common Named Entity Recognition (NER) task. Neural language models provide a great improvement in Natural Language Processing (NLP) tasks, such as NER, when they are integrated with neural network methods. This paper evaluates the use of current state-of-the-art deep learning methods (Bi-LSTM-CRF) in the task of identifying patient names in clinical notes, for de-identification purposes. We used two corpora and three language models to evaluate which combination delivers the best performance. In our experiments, the specific corpus for the de-identification of clinical notes and a contextualized embedding with word embeddings achieved the best result: an F-measure of 0.94.